2021
DOI: 10.1155/2021/6648247
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Status of Bacteria from a Health Facility in Ghana: A Retrospective Study

Abstract: Background. Regardless of the global concerted effort to control the development and spread of antimicrobial resistance, increasing cases are continually documented at many medical centres. This situation is reinforced by inadequate information on the trend of resistance resulting from lack of regular antimicrobial resistance surveillance. The present study sought to detect the number of multidrug-resistant (MDR), extended drug-resistant (XDR), and pandrug-resistant (PDR) bacterial isolates at a health facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The facility serves as a referral diagnostic centre in the Central Region of Ghana. This study is a retrospective analysis of routine recovered bacterial isolates subjected against a panel of antibiotics for susceptibility testing 25 . The study spun from January to December 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The facility serves as a referral diagnostic centre in the Central Region of Ghana. This study is a retrospective analysis of routine recovered bacterial isolates subjected against a panel of antibiotics for susceptibility testing 25 . The study spun from January to December 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Possibly, this is due to the lack of clear definitions based on national data (Yevutsey et al, 2017). When we applied the data to other definitions of MDR, such as the German KRINKO definitions and the University Hospital Zurich classification (Wolfensberger et al, 2019;Wolfensberger et al, 2019), no MDR was identified (data not shown), which is contrary to a previously published report in Ghana (Inusah et al, 2021). Possibly, this is due to the limited number of antibiotics tested for resistance.…”
Section: Multidrug Resistance Isolates As Defined By Ecdc-mdrmentioning
confidence: 60%
“…Strains isolated from food animals also show antibiotic resistance, threatening food security [46]. Therefore, it is urgent to put in place rapid and effective strategies to control antibiotic resistance [47].…”
Section: Status Of Amr In Burkina Fasomentioning
confidence: 99%